Integration of Foreign Languages and Professional Sciences in the Process of Vocational Education on the Basis of Clil Technology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
CLIL (Content and Language Integrated Learning) is a technology of integrated learning of content and language, which is used in situations of teaching special subjects and parts of special subjects in a foreign language, that is, the goal is dual teaching of the subject: learning the subject and learning a foreign language at the same time. In this article, the integration of foreign language and professional subjects on the basis of CLIL technology in the process of vocational education is studied.